Oculodentodigital Dysplasia: A Case Report and Major Review of the Eye and Ocular Adnexa Features of 295 Reported Cases - Virang Kumar; Natario L. Couser; Arti Pandya (Case Reports in Ophthalmological Medicine)
Oculodentodigital dysplasia (ODDD) is a rare genetic disorder associated with a characteristic craniofacial profile with variable dental, limb, eye, and ocular adnexa abnormalities. We performed an extensive literature review to highlight key eye features in patients with ODDD and report a new case of a female patient with a heterozygous missense GJA1 mutation (c.65G>A, p.G22E) and clinical features consistent with the condition. Our patient presented with multiple congenital anomalies including syndactyly, microphthalmia, microcornea, retrognathia, and a small nose with hypoplastic alae and prominent columella; in addition, an omphalocele defect was present, which has not been reported in previous cases. A systematic review of the published cases to date revealed 91 literature reports of 295 individuals with ODDD. There were 73 different GJA1 mutations associated with these cases, of which the most common were the following missense mutations: c.605G>A (p.R202H) (11%), c.389T>C (p.I130T) (10%), and c.119C>T (p.A40V) (10%). Mutations most commonly affect the extracellular-1 and cytoplasmic-1 domains of connexin-43 (gene product of GJA1), predominately manifesting in microphthalmia and microcornea. The syndrome appears with an approximately equal sex ratio. The most common eye features reported among all mutations were microcornea, microphthalmia, short palpebral fissures, and glaucoma.